PENGARUH RESIDU UREA DAN KOMPOS DENGAN APLIKASI KOMPOS KOTORAN KAMBING TERHADAP SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN OKRA PADA TANAH TERDAMPAK LETUSAN GUNUNG KELUD - Akhmad Sihab Ulumuddin; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
A study that was aimed at elucidating the effect of Urea and compost residue with application goat manure compost on soil chemical properties and growth of Okra (Abelmoschus esculentus) on soil impacted by eruption of Mount Kelud, was conducted in a glasshouse. Treatments tested in this study were applications of residue urea and compost with application of goat manure (1/3 weight planting media) A1: 2/3 residual soil (100% urea); A2: 2/3 residual soil (100% poultry manure compost) A3: 2/3 residual soil (100% cow manure compost); A4: 2/3 residual soil (50% urea + 50% poultry manure compost); A5: 2/3 residual soil (50% urea + 50% cow manure compost). The five treatments were arranged in a completely randomized design with three replicates. Â The results showed no significant effect on soil chemical properties of pH, C-organic, and CEC of the Mount Kelud eruption-impacted soil at 4 and 8 weeks after incubation (WAI), except for C/N ratio at 4 WAI. However, urea and compost residues with application goat manure had significant effect on plant height at 4, 6, and 8 weeks after planting (WAP), and number of leaves at 8 WAP. A3 (2/3 residual soil 100% cow manure compost + 1/3 goat manure) gave the highest number of leaves (13) at 8 WAP, and A5 (2/3 residual soil 50% urea + 50% cow manure compost + 1/3 goat manure), and gave the highest of plant height respectively with 28,83 cm; 47,33 cm; 55,17 cm at 4, 6, and 8 WAP.